MENGEMIS ONLINE PERSEPEKTIF HUKUM ISLAM (Faculty of Law, University of Palembang, 2023)
Abstrac The development of technology has a very big impact on human life, including creativity and source of income. Recently, Indonesia was shocked by the circulation of online begging videos on the tiktok application, by doing the challenge of soaking in mud, pouring the body with cold water for hours and soaking in a poll. In this activity, the challenge actors will geb and ask the audience to give a lot of gift, the more gifts the audience gives, the more money they will get. This has received a lot of attention from the public, the government dan aven religious leaders. There is also a method used, namely a literature review in the from of videos, newspapers, magazines, reference books, and others as. The results of the study are the described in accordance with the facts. The results of the study revealed that in Islam, begging is a despicable act and is forbidden if there is no element of compulsion or urgent need. Because the act of begging is tantamount to being lazy at work and trying and degrading oneself dignity and degree. What’s more, if the begging is accompanied by deceit to attract people’s sympathy to give alms. Likewise, the law of begging online is the same as begging in general, which is haram because in general they also beg through social media.